2018
DOI: 10.1021/acsomega.8b00194
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Mechanical, Electrical, and Thermal Properties of Polymer Nanocomposites through GMA Bridging at Interface

Abstract: Polymer nanocomposites (PNCs) have become an exciting field of current research and have attracted a huge interest among both academia and industry during the last few decades. However, the multifunctional single-nanocomposite film exhibiting the combination of desired structure and properties still remains a big challenge. Herein, we report a novel strategy to address these problems by using versatile polymer glycidyl methacrylate (GMA) as a bridging medium between the filler and the polymer matrix, resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…In addition to microstructure and density tunability, preheating treatment greatly affected the fraction of hydrogen bond formation at the fiber–matrix interface. The hydrogen bonds are responsible for strengthening the intramatrix (i.e., between amylopectin molecules) and fiber–matrix interfaces. , Such a strengthening mechanism contributes significantly to the composite’s mechanical properties. Hydrogen bonding forms when hydroxyl (OH) and carboxylic acid (COOH) groups are present in fibers and matrix. ,, Figure d shows FTIR spectra for 6–14 min preheated samples. The O–H stretch for a hydroxyl group appeared as a band in the region of 3000–3600 cm –1 , centered at about 3299 cm –1 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to microstructure and density tunability, preheating treatment greatly affected the fraction of hydrogen bond formation at the fiber–matrix interface. The hydrogen bonds are responsible for strengthening the intramatrix (i.e., between amylopectin molecules) and fiber–matrix interfaces. , Such a strengthening mechanism contributes significantly to the composite’s mechanical properties. Hydrogen bonding forms when hydroxyl (OH) and carboxylic acid (COOH) groups are present in fibers and matrix. ,, Figure d shows FTIR spectra for 6–14 min preheated samples. The O–H stretch for a hydroxyl group appeared as a band in the region of 3000–3600 cm –1 , centered at about 3299 cm –1 .…”
Section: Resultsmentioning
confidence: 99%
“…Conductive polymers are alternative nanomaterials that can help overcome energy crises the world is facing and sustain viable environmental and climatic conditions. These nanomaterials show not only metal-like but also semiconductor properties with π-conjugated hetero (aromatics) capable of transporting charges and efficiently interacting with light. The good biocompatibility of polymers has enhanced microorganism viability in biohybrid systems because the interaction between polymer and microorganism is only Coulombic interactions and hydrophilicity and is affected by polymer structure and surface of microorganism . Thus, organic-conjugated polymers may offer excellent opportunities to develop efficient CO 2 -to-multicarbon conversion biohybrid systems.…”
Section: Overview Of Polymer-based Nanomaterials In Pbssmentioning
confidence: 99%
“…The alteration of plastic to rubber-like material can be set in polymer material with adjusting glycerol content in hydrogen-bounded poly­(vinyl alcohol)-glycerol intermolecular complexes . Not only mechanical properties but also electrical and thermal properties of polymer is tunable by additional doping or modification bridging agent interface between polymer matrix and filler . Thus, polymers are naturally insulator tunable to conductive.…”
Section: Overview Of Polymer-based Nanomaterials In Pbssmentioning
confidence: 99%
See 1 more Smart Citation
“…Kumar et al demonstrated that the effect of glycidyl methacrylate (GMA) was pronounced in shifting the melting temperature of PLA–PBAT compounds, although its influence on toughening PLA was very limited. In fact, GMA can act as a bridging medium between fillers and polymeric matrices, strengthening the interfaces . Likewise, ethylene-methyl acrylate-glycidyl methacrylate (EMA-GMA), an inexpensive commercial compatibilizer, may contribute to bond formation between its epoxy-terminated groups and the hydroxyl end-groups in PLA.…”
Section: Introductionmentioning
confidence: 99%